High Blood Ammonia Levels Associated with Long-term Valproic Acids Therapy in Epileptic Children - I Gusti Lanang Sidiartha; I Gusti Ngurah Made Suwarba; Dyah Kanya Wati; Ida Bagus Subanada (Molecular and Cellular Biomedical Sciences, 2020)
Background: Valproic acid is an effective drug for controlling seizure in children with epilepsy and it is usually used for treatment as long as two years or more. Blood ammonia level often increased in epileptic children who were treated with long-term valproic acid. The study was conducted to determine the relationship between blood ammonia level with valproic acid therapy in epileptic children.Materials and Methods: This is an observational study with cross-sectional approach. The subjects were 64 children with epilepsy, average age of 6.2 years old. Subjects were 33 boys and 31 girls. Blood ammonia level was examined using enzymatic glutamate dehydrogenase. Subjects were divided into 2 therapeutic groups based on the duration, doses and combination therapy of valproic acid. Subjects were recruited from Pediatric Neurology Clinic, Sanglah General Hospital, Bali, Indonesia, from May to December 2017. Comparison of blood ammonia level between groups were analyzed using an Independent t-test with significances if the p<0.05.Results: A significant difference of blood ammonia level was found between subjects who were treated with valproic acid less than 2 years and more than 2 years (45.7±16.4 mmol/L vs. 70.9±43.6 mmol/L; p=0.032). However, significant difference was not found between the groups according to the doses and combination therapy (p=0.450 and p=0.647, respectively).Conclusion: Blood ammonia level was significantly higher in epileptic children who used long-term valproic acid, hence it was recommended to check the blood ammonia level routinely.Keywords: ammonia, epilepsy, valproic, children